2004
DOI: 10.1080/01926230490266000
|View full text |Cite
|
Sign up to set email alerts
|

Zonal Distribution of Cell Proliferation in the Liver of Untreated B6C3F1 and C57BL Mice

Abstract: To determine the lobular distribution of hepatocellular proliferation, S-phase response was measured in untreated adult male B6C3F1 and C57BL mice at ages 11, 14, and 23 weeks. The percentage of cells in S-phase (labeling index, LI) was evaluated using immunohistochemical detection of 5-bromo-2 -deoxyuridine (BrdU). The BrdU was delivered either by a single ip injection 2 hr prior to sacrifice or via an osmotic minipump implanted subcutaneously for 3 or 7 days. Mitotic and apoptotic indices were determined on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
6
0
1
Order By: Relevance
“…Zonal differences in cell proliferation in the liver occur during fetal development, postnatal growth and homeostasis in the adult organ. 3738 If tissue progenitor cells are at greater risk of mutation during fetal development, mutant cells emerging from these populations would be expected to increase the MF in the tissue, which could account for the observed increase in MF at the ten-week time point.…”
Section: Discussionmentioning
confidence: 99%
“…Zonal differences in cell proliferation in the liver occur during fetal development, postnatal growth and homeostasis in the adult organ. 3738 If tissue progenitor cells are at greater risk of mutation during fetal development, mutant cells emerging from these populations would be expected to increase the MF in the tissue, which could account for the observed increase in MF at the ten-week time point.…”
Section: Discussionmentioning
confidence: 99%
“…[24,25] Specific spatial patterns of hepatocyte replication were reported for rodent liver. [11,14,26] A heterogeneous distribution of DNAs in the liver of hepatectomized rats with the highest proliferative rate in periportal hepatocytes was demonstrated. [7,14] In agreement with this, we found that values of DNAs in the PPH of hepatectomized livers were statistically different from those in the PVH at 42 and 46 hr PH, with the highest values in PPH ( Table 2).…”
Section: Discussionmentioning
confidence: 94%
“…[10] Administration of bromodeoxyuridine (BrdU) is used to determine the S-phase response in cell proliferation studies. [11] In addition, studies performed in adult normal liver have found that S-phase hepatocytes are localized at all segments of the lobule, [12] and that their turnover occurs randomly throughout the lobule. [13] However, other reports have indicated that the hepatocytes subpopulation in rat regenerating livers, synthesizes DNA with a heterogeneous distribution, and that cell proliferation is highest in the periportal area and decreases toward the draining vein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the zonal distribution of DNA synthesis in the rat liver is known (Barrass et al, 1993) and that Barrass has established a reliable method to study this, gave reason to make similar studies on mouse liver, as there are no directly comparable data in mice (Burkhardt et al, 2004). …”
Section: Section 42 Zonal Distribution Of Dna Synthesis In Livermentioning
confidence: 99%